Zn and Pb marking of Ca binding to humic substances and PHREEQC speciation simulations - Bosire, G. O.; Ngila, J. C. (IWA Publishing, 2016)
Power generating companies using and recycling cooling water usually experience deposition of insoluble salts on pipes carrying the water, leading to scaling problems. By controlling parameters that optimize competitive Ca complexation, the scaling potential could be reduced. This semiempirical study determined the effect of ligands in binding, as well as the optimum parameters for Ca complexation experimentally using simulated water solutions before modelling. Experimental results showed that metal binding to ligands depended on the type of metal in competition, the pH and the humic substance used. Zn and Pb voltammetric peaks decreased with the addition of humic acid, tannic acid and catechol. Ca showed a synergistic phenomenon in the form of increased peak heights of the trace cations. Using PHREEQC model saturation index output results, the mineral phases likely to precipitate were successfully described. Furthermore, the effect of changing pH on scale formation was determined. For example, we successfully described the influence of pH on speciation and complexation through the formation of H-humate and humate2 . The models showed that pH may be manipulated to govern the incidence of scale. Predictive models were derived to determine what would be a useful tool in reducing the potential for scaling.
Keywords: PHREEQC; saturation indices